Analisis Peran Petugas Loading Master PT Gapura Angkasa Dalam Penanganan Kargo Udara di Bandar Udara Internasional Adi Soemarmo Solo - Wyananda Namira Shafa; Desiana Rachmawati (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This research aims to find out: how baggage carried by passengers is not free from various problems with baggage service deviations, which usually occur when passengers arrive at the final destination station or during post-flight service, this can be one of the performance benchmarks for a ground handling company. , whether it is good or not in providing service to passengers. In this case, the role of the loading master officer plays an important role in the process of loading and unloading cargo, preventing unwanted things from happening. This study used qualitative research methods. The data collection techniques used were, observation, interviews, documents, and documentation along with observations. The researcher directly carried out observations, the researcher also explained the results of the data taken during interviews and observations. For the interview, the researcher interviewed the Loading Master officer 3 sources with document data obtained by the researcher. from documentation of the activities of Loading Master officers when carrying out their duties and responsibilities in the field and also in the form of implementation documents for the data analysis techniques used, namely data collection, data reduction, data presentation, discussion, and conclusions. The role of Loading Master officers is very important at Adi Soemarmo Solo Airport, both from the implementation of standard operational procedures and also influences improving the performance of Loading Master officers for air cargo handlers. Not only that, researchers also found that Loading Master officers are very fast in Loading-Unloading if officers are slow or if you are not careful during the Loading-Unloading process, it will result in the plane being delayed.